Association of Waiting Time for Diagnosis with Quality of Life (QoL) in Nasopharyngeal Carcinoma: A Survey in Dharmais Cancer Hospital - Fifi Dwijayanti; Nuryanti Samosir; Cita Herawati (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Cancer patients experience many symptoms. The symptoms have a major impact on Quality of Life (QoL) among patients with nasopharyngeal carcinoma. Diagnostic and treatment delays can be reduced to improve the prognoses of the cancer patients. Cancer waiting time may still be important as indicators of overall performance of a health service. Objective: The aim of this study was to investigate the association of waiting time for diagnosis with quality of life in nasopharyngeal carcinoma. Methods: A cohort survey was done in six months from July to December 2019. We conducted new patients whom never had any therapy from other care centers. Data were collected two times using the structured interview technique by using EORTC QLQ-C30 and QLQ-H&N43 questionnaires. We counted the time for diagnosis from the first time the patient came for diagnostic until the first therapy for the cancer. Results: The eligible samples were 24 patients. Their mean (SD) and median ages were 46.71 (10.1) and 49.0 years respectively and waiting time for diagnosis was 34.2 (10.4) and 31.0 days. The patient’s scored <33.3 for global health status in first came to the hospital (pre-test) was 66.7%. In pre-test, diarrhea and constipation were the most disturbing symptoms and the post-test were loss of appetite and dyspnea. Time for diagnosis was statistically significant with global health (P<0.05). Global health has significant differences in the pre-test and post-test. Conclusion: The nasopharyngeal carcinoma patients in our institution had a worse quality of life regarding overall status. Waiting time for diagnosis has association with global health score in quality of life (QoL). Further research is required to investigate the clinical patient during waiting period for diagnosis.